Utilization of non-pneumatic anti-shock garment for the management of obstetric hemorrhage among healthcare providers in north Shewa zone, Ethiopia - Taye, Birhan Tsegaw; Silesh Zerihun, Mulualem; Moltot Kitaw, Tebabere; Amogne, Fetene Kasahun; Kindie Behulu, Geremew; Lemma Demisse, Tesfanesh; Chekole, Moges Sisay; Fitie, Girma Wogie; Worku, Solomon Adanew; Kibiret, Desta Mekete; Ferede, Addisu Andualem; Bejtual, Kalkidan; et al. (Frontiers in Public Health, 2023)
Background: Maternal mortality is increasing tragically globally. Obstetric hemorrhage (OH) remains the major cause of maternal deaths. Non-Pneumatic Anti-Shock Garment (NASG) has several positive results in the management of obstetric hemorrhage in resource-limited settings where getting definitive treatments are difficult and limited. Therefore, this study aimed to assess the proportion and factors associated with the utilization of NASG for the management of obstetric hemorrhage among healthcare providers in the North Shewa zone, Ethiopia. Methods: A cross-sectional study was conducted at health facilities of the north Shewa zone, Ethiopia from June 10th-30th/2021. A simple random sampling (SRS) technique was employed among 360 healthcare providers. Data were collected using a pretested self-administered questionnaire. EpiData version 4.6 and SPSS 25 were used for data entry and analysis, respectively. Binary logistic regression analyses were undertaken to identify associated factors with the outcome variable. The level of significance was decided at a p-value of <0.05. Results: The utilization of NASG for the management of obstetric hemorrhage among healthcare providers was 39% (95%CI: 34- 45). Healthcare providers who received training on NASG (AOR= 3.3; 95%CI: 1.46,-7.48), availability of NASG in the health facility (AOR= 9.17; 95%CI: 5.10-16.46), had a professional qualification of diploma (AOR= 2.63; 95%CI: 1.39- 3.68), had a professional qualification of bachelor degree (AOR= 7.89; 95%CI: 3.1-16.29)and those healthcare providers who have a positive attitude towards utilization of NASG (AOR= 1.63; 95%CI: 1.14-2.82) were variables positively associated with the utilization of NASG. Conclusion: In this study, almost two-fifths of healthcare providers used NASG for the management of obstetrics hemorrhage. Arranging educational opportunities and continuous professional development training for healthcare providers, providing in-service and refresher training, and making it available at health facilities may help healthcare providers to effectively use the device, thereby reducing maternal morbidity and mortality.